2022
DOI: 10.1038/s41598-022-12754-9
|View full text |Cite
|
Sign up to set email alerts
|

Applications of machine learning in pine nuts classification

Abstract: Pine nuts are not only the important agent of pine reproduction and afforestation, but also the commonly consumed nut with high nutritive values. However, it is difficult to distinguish among pine nuts due to the morphological similarity among species. Therefore, it is important to improve the quality of pine nuts and solve the adulteration problem quickly and non-destructively. In this study, seven pine nuts (Pinus bungeana, Pinus yunnanensis, Pinus thunbergii, Pinus armandii, Pinus massoniana, Pinus elliotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Arndt et al [ 52 ] and Arndt et al [ 42 ] developed multiclass models to determine the geographical origin of almonds using SVM, which is a method that can be used to train linear and non-linear classifiers, for classification [ 77 ]. Huang et al [ 59 ] also used machine learning methods, such as the RF, NB, or the multilayer perceptron (MLP), to identify the cultivars of pine nuts. Menevseoglu et al [ 36 ] successfully identified ground almonds that had been adulterated with apricot kernels by applying different machine learning algorithms.…”
Section: Strategies For the Treatment Of The Nir Data And Chemometric...mentioning
confidence: 99%
“…Arndt et al [ 52 ] and Arndt et al [ 42 ] developed multiclass models to determine the geographical origin of almonds using SVM, which is a method that can be used to train linear and non-linear classifiers, for classification [ 77 ]. Huang et al [ 59 ] also used machine learning methods, such as the RF, NB, or the multilayer perceptron (MLP), to identify the cultivars of pine nuts. Menevseoglu et al [ 36 ] successfully identified ground almonds that had been adulterated with apricot kernels by applying different machine learning algorithms.…”
Section: Strategies For the Treatment Of The Nir Data And Chemometric...mentioning
confidence: 99%
“…Consequently, some scholars have started to explore the fusion of information from multiple types of features to perform classification discrimination tasks. Huang [27] Hyperspectral ELM 5 types of wheat 86.26% Bao [28] RGB MLP, LDA, SVM etc. 5 types of maize Each model achieved 93% Xu [29] Deep learning RGB MF Swin-Transformer 19 types of maize 96.47% Bi [30] Hyperspectral image CNN-LSTM 5 types of maize 95.26% Wang [31] NIRS CNN, RNN, LSTM, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of non-destructive [11][12][13] detection of forest seeds using electromagnetic waves from different regions increases with the assessment of each single seed [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] individually, determined by the focal distance [33] from the sensor to the place of reflection of the electromagnetic beam from the top of the seed coat [34]. At the same time, depending on the type and nature of exposure to electromagnetic radiation, the biophysical [13,35] (spectrometric) parameters of the seed correlate with different properties and indicators of a single seed [2,5,7,9,11,12,[12][13][14][15][16]21,[23][24][25][26][27][28]31,34,…”
mentioning
confidence: 99%
“…Esteve Agelet et al (2014) conclude from a systematic search of 168 references for the identification of a single seed that "although no measurement mode (reflectance, transmittance) have lead to the best re-ported calibrations, when dealing with heterogenic seeds reflectance is the best working mode [123]". Most studies of the forest single seed [14][15][16]20,21,24,[26][27][28][29][30][31][32]99,123,136]. Expensive devices are used to create and detect electromagnetic radiation with long exposure.…”
mentioning
confidence: 99%